2013
DOI: 10.1590/s1677-5538.ibju.2013.04.03
|View full text |Cite
|
Sign up to set email alerts
|

Is there a relationship between severity of coronary artery disease and severity of erectile dysfunction?

Abstract: Introductıon:The correlation between erectile dysfunction (ED) and coronary artery disease has been emphasized and ED has been recognized as a potential independent risk factor and/or predictor of coronary artery disease (CAD). We evaluated the association between the number of occluded coronary arteries in myocardial infarction (MI) patients with the severity of ED, and investigated the influence of related risk factors in our study group. Materials and Methods: 183 male patients who underwent coronary angiog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 26 publications
1
17
2
Order By: Relevance
“…Accordingly, they concluded that CAC score increased as the severity of ED increased. On the other hand, Canat et al [28] investigated the relationship between ED and CAD in terms of number of occluded vessels and evaluated 183 patients who underwent angiography after acute myocardial infarction. They reported no difference between the patient groups with one vessel occluded, two vessels occluded, and three vessels occluded in terms of risk factors (age, waist circumference, lipid profile, diabetes, and smoking) excluding hypertension.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, they concluded that CAC score increased as the severity of ED increased. On the other hand, Canat et al [28] investigated the relationship between ED and CAD in terms of number of occluded vessels and evaluated 183 patients who underwent angiography after acute myocardial infarction. They reported no difference between the patient groups with one vessel occluded, two vessels occluded, and three vessels occluded in terms of risk factors (age, waist circumference, lipid profile, diabetes, and smoking) excluding hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Angiograms of the patients were scored and divided into three groups according to the SS as low (SS ≤22), intermediate (SS between [23][24][25][26][27][28][29][30][31][32], and high (SS ≥33) [8]. After coronary angiography, erectile performance statuses of all patients were evaluated using the International Index of Erectile Function (IIEF), which is a validated 15-item self-administered questionnaire [10].…”
Section: Methodsmentioning
confidence: 99%
“…The pathogenesis of diabetic ED is complex. Diabetic angiopathies include macrovascular disease, microvascular disease and endothelial dysfunction, which are all known to be involved in the pathophysiological process of ED (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is believed that ED and coronary artery disease (CAD) are clinical manifestations of the same pathophysiological process, product of a severe endothelial dysfunction [10][11][12]. In the study conducted by Demirkol S et al, it was found that erectile function was signi icantly decreased in patients who presented both microvascular angina (syndrome X) and CAD, thus they conclude that ED and syndrome X are manifestations of a common vascular phenomenon that includes endothelial dysfunction as the mechanism underlying both conditions [4].The pathophysiology of microvascular angina has not been clearly elucidated, although several abnormalities have been proposed including: alteration in coronary low reserve, insulin resistance, abnormal autonomic control and microvascular spasm; all these, also associated with endothelial dysfunction, which is another traditional risk factor for cardiovascular disease and occurs before the development of apparent functional or structural systemic vascular disease [6,12]. It is characterized by a decrease in the bioavailability of endogenous nitric oxide (NO) and increase in plasma levels of endothelin-1, promoting in turn an increase in oxidative stress and vasoconstrictor mediators such as angiotensin II, causing generalized damage in the vascular endothelium, being the arteries of the penis more susceptible due to their size and therefore affected earlier 4 .…”
mentioning
confidence: 99%
“…Therefore, it is believed that ED and coronary artery disease (CAD) are clinical manifestations of the same pathophysiological process, product of a severe endothelial dysfunction [10][11][12]. In the study conducted by Demirkol S et al, it was found that erectile function was signi icantly decreased in patients who presented both microvascular angina (syndrome X) and CAD, thus they conclude that ED and syndrome X are manifestations of a common vascular phenomenon that includes endothelial dysfunction as the mechanism underlying both conditions [4].…”
mentioning
confidence: 99%